Solve for n.
-53 + n = -28
-35
-25
25
35

Question

Asked 1/18/2013 3:30:59 PM

Updated 5/29/2014 9:23:45 PM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [5/29/2014 9:23:45 PM]

s

vchutkan|Points 5734|

debnjerry|Points 42983|

nicolevaughan16|Points 156|

ramkitten|Points 7315|

Dolphinlover97|Points 31|

Dolphinlover97|Points 31|

Dolphinlover97|Points 31|

jameshand|Points 2049|

shifa saleheen|Points 9931|

Afzal82|Points 0|

(9x - 3) + (6 - 2x) = 0

7x + 3 = 0

7x = -3

x = -3/7

spyderman|Points 651|

brenda143|Points 141|

dennis003|Points 1000|

Fanboy|Points 2821|

brenda143|Points 141|

Neon Aloo|Points 635|

batotoy|Points 1475|

Ambomoonu|Points 285|

debnjerry|Points 42989|

batotoy|Points 1475|

Question

Asked 1/18/2013 3:30:59 PM

Updated 5/29/2014 9:23:45 PM

4 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [5/29/2014 9:23:45 PM]

Rating

3

-3x = -15

x = -15/-3

x = 5

x = -15/-3

x = 5

Added 5/29/2014 9:19:09 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/29/2014 9:28:02 PM]

3

5x - 1 = 26

5x = 26 + 1

5x = 27

x = 27/5

5x = 26 + 1

5x = 27

x = 27/5

Added 5/29/2014 9:19:49 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/29/2014 9:27:33 PM]

3

x/2 = -5

x = -5(2)

x = -10

x = -5(2)

x = -10

Added 5/29/2014 9:20:14 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/29/2014 9:28:26 PM]

3

5(2x - 1) = 6

10x - 5 = 6

10x = 6 + 5

10x = 11

x = 11/10

10x - 5 = 6

10x = 6 + 5

10x = 11

x = 11/10

Added 5/29/2014 9:21:07 PM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/29/2014 9:36:22 PM]

31,870,193

questions answered

There are no comments.